Factors That Influences Mental Health Policy In Albania - Eneida Frasheri; Eris Dhamo (European Scientific Journal, ESJ, 2016)
Mental health policy is a major challenge in every government engagement. Human wellbeing is threatened by mental health issue, and this is why it is necessary to position mental health as a health priority (WHO, 2001). The reduction of human and economic cost of mental health problems can be achieved by providing equitable and evidence-based mental healthcare and treatment. In Albania, the organization of mental health policy has experienced changes in the past half century, especially after the 90’s. This was driven by political commitment at national and intergovernmental levels in response to the challenges posed by mental health problems. The purpose of this paper is to analyze, present factors, and circulates what affects and prepossess the adoption of new mental health policy. The methodology used for this paper was based on two main elements. The first was the analyzing of Albanian conceptual framework, which is derived from two grounded elements: policy content and health policy process. The second element involves data collection using semistructured interview (12) with three levels of policy: policymakers, health policy administrator, and mental health care provider. Also, we consulted a wide range of electronic databases before underpinning the research with additional search. This search includes the scanning of a range of websites, reference lists of included studies, the legal mental health framework, and the respective documents. The activities stipulated in the First Component of the South-Eastern European Mental Health Project under the Stability Pact urged the process of a new mental health policy formulation and adoption of mental health legislation stressing human rights of patients. The WHO has influenced the whole mental health policy framework. They have instructed the National Policy Document for the Mental Health and the recpective action plans. In addition, they have supervised the impemention of this Documents and has trained mental health experts at all levels. Albanian policymaker are concerned with having an adequate map of mental health facilities. This is because many of the dedicated program are far way to be reached from persons in need. All policymaker actors are focused on the need for identification. In this trend of increase in the number of persons with mental health problems and their need for a more holistic care, finances has a crucial role to play.